2016
DOI: 10.1371/journal.pone.0152749
|View full text |Cite
|
Sign up to set email alerts
|

Association between Obstructive Sleep Apnea and Community-Acquired Pneumonia

Abstract: BackgroundWe hypothesized that obstructive sleep apnea (OSA) can predispose individuals to lower airway infections and community-acquired pneumonia (CAP) due to upper airway microaspiration. This study evaluated the association between OSA and CAP.MethodsWe performed a case-control study that included 82 patients with CAP and 41 patients with other infections (control group). The controls were matched according to age, sex and body mass index (BMI). A respiratory polygraph (RP) was performed upon admission for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 32 publications
2
41
1
1
Order By: Relevance
“…Although the study's main outcome (a broad composite of variables associated with post-operative mortality and a range of post-operative complications) showed no discrepancy between the group with excessive SDB and the group with a normal or near-normal SDB, this was not true of the incidence of sepsis and pneumonia, which were higher, particularly in the untreated forms of moderate to severe sleep apnoea. This association between sleep apnoea and various infections, already demonstrated by other previous studies [4,6,7], emphasises the importance of moving beyond an exclusive focus on the analysis of the cardiovascular impact of sleep apnoea (even in patients with a high cardiovascular risk, as in the study in question) and exploring other possibilities in which SDB could have potentially preventable or treatable consequences.There is a sufficiently plausible biological explanation for an increase in the number of post-operative infectious complications in patients with sleep apnoea. The coordination between respiration and swallowing…”
supporting
confidence: 61%
“…Although the study's main outcome (a broad composite of variables associated with post-operative mortality and a range of post-operative complications) showed no discrepancy between the group with excessive SDB and the group with a normal or near-normal SDB, this was not true of the incidence of sepsis and pneumonia, which were higher, particularly in the untreated forms of moderate to severe sleep apnoea. This association between sleep apnoea and various infections, already demonstrated by other previous studies [4,6,7], emphasises the importance of moving beyond an exclusive focus on the analysis of the cardiovascular impact of sleep apnoea (even in patients with a high cardiovascular risk, as in the study in question) and exploring other possibilities in which SDB could have potentially preventable or treatable consequences.There is a sufficiently plausible biological explanation for an increase in the number of post-operative infectious complications in patients with sleep apnoea. The coordination between respiration and swallowing…”
supporting
confidence: 61%
“…OSA patients are predisposed to increased microaspiration and gastric reflux, [ 15 ] and it has been reported that OSA patients had an increased risk of community-acquired pneumonia. [ 16 ] Therefore, the current study was designed to investigate lower airway microbiota in OSA patients in comparison to that of control subjects with respiratory diseases other than OSA. We demonstrated that there was diverse microbiome in the airways of OSA patients and control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical data suggest that OSA could be associated with a higher incidence of cancer, tumour aggressiveness and cancer mortality [2][3][4]. In addition, OSA has been related to the severity of community-acquired pneumonia [5]. It has been proposed that hypoxia-induced immune deregulation might be responsible for many of these alterations [6].…”
Section: Introductionmentioning
confidence: 99%